Marine Sponge Jaspis sp, A Potential Bioactive Natural Source against Infectious diseases - Puji Astuti Puji Astuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: The high incidence of microbial infection and the emergence of drug resistant and multidrugresistant microbes as well as the lack of any current chemotherapy augmented the necessity to search for new and better antimicrobial drug. Marine invertebrates are known as rich sources of compounds with unique chemical structures and pronounced chemical and biological activities, which suggests potential value as lead structures for the development of new pharmaceuticals.Objective: This study aims to screen potential antiinfective of sponges extracts collected from Barrang Lompo island and report on their antibacterial and antifungal properties.Methods: Testing for anti-infective agents was conducted using dilution method. Nutrient Agar was used as the testing media and nutrient broth for the inoculation of microorganisms. Staphylococcus aureus, Escherichia coil and Salmonella thypi were used as the testing bacteria and Candida albicans for the testing fungi. Chloramphenicol was used as positive control for antibacterial testing and ketocozaole for antifungal testing.Results: From the 11 acetone extracts tested, BL-02, BL-09, BL-10 and BL-12 was found to inhibit the growth of microorganisms and the extract of BL-10 was found to be the most active. Bioautography results suggest that the polar fractions were responsible for the growth inhibition.Conclusion: the polar fraction of acetone extract of BL-10 was considered to be potential compounds for further characterization as anti infective agents.Key words: screening, sponge, antibacteria, antifungi